MULTIPLE MODALITIES OF ARACHNOID CYST TREATMENT AND POSSIBLE COMPLICATIONS - Milošević, Predrag (Acta medicae Medianae, 2021)
Arachnoid cysts are benign, congenital lesions of the brain that grow inside the leaves of the arachnoid. They represent 1% of all intracranial mass lesions and are most frequently detected during childhood and adolescence. In most cases, they do not cause any symptoms. However, they can grow to a large size and cause life-threatening symptoms, especially if they grow in a confined space such as a posterior cranial fossa.Our case is a symptomatic arachnoid cyst of the posterior cranial fossa in a 22-godišnjeg year old man. The patient had symptoms and signs of progressive intracranial hypertension. CT of the brain showed the presence of an arachnoid cyst in the posterior cranial fossa that compresses the surrounding structures. The cyst was surgically treated with suboccipital craniectomy, excision of the cyst wall and drainage.In our study, we examined the simultaneous use of different methods of arachnoid cyst drainage and their complications.The goal was to show that the simultaneous use of multiple alternative methods of surgical treatment of these cysts has an advantage over the single treatment method, because of the lower possibility of recurrence.
Keywords: arachnoid cyst; treatment modalities; intracranial hypertension